Global Trends Research on Urgency of Inclusive Education and It’s Thematic Mapping: A Systematic Literature Review - Muhammad Fikri Fauzi Faize; Nadia Amalia (ITScience (Information Technology and Science), 2026)
Inclusive education is a form of education that upholds the values of equality and equal rights, ensuring that every child receives an education, regardless of physical or cognitive limitations. This study aims to analyze global trends in 'inclusive education' using the PRISMA method from 2017 to 2026, drawing on the Dimensions AI database. The data was accessed on February 7, 2026, by entering the keyword